A Study On Development Of A Concrete Brick Using Plastic PET Bottles As Fine Aggregates Using Solidworks Software - Wan Daud, Syed Abdul Hafiz; Ali, Roslinda; Marsi, Noraini (Progress in Engineering Application and Technology, 2021)
Plastic is an organic polymer which usually made from synthetic. Plastic is a material that either cannot be totally decomposed or takes a long time to decompose. This study is interested to evaluate the mechanical and physical properties of PET bottles using different ratio of 20%, 40%, 60%, and 80% in producing a concrete brick. Different ratio of PET concrete bricks will undergo the mechanical and physical testings to determine the effectiveness of plastic waste by using Solidwork software simulation. The two tests conducted for the mechanical testing included compressive strength test and sound absorption test while for the physical testing, the tests conducted were density and porosity tests. From the test result recorded, the value from the comppresive strength test and density test carried out decreased when the percentage of PET increased. Meanwhile, the value of porosity test increase when the percentage of PET increase. It can be concluded that the optimum percentage for replacement fine aggregate with PET plastic waste for this study is 20%.